2011
DOI: 10.1007/s10658-011-9824-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal effects of cultivar mixtures on wheat stripe rust epidemics

Abstract: The use of cultivar mixtures is increasingly practical in wheat stripe rust management. Field experiments with wheat cultivar mixtures were conducted to determine their effects on temporal and spatial patterns of stripe rust epidemics in three regions. In the Beijing and Gangu fields, where the epidemics were caused by artificial inoculation, disease incidence and the area under the disease progress curve (AUDPC) of the cultivar mixtures were significantly lower (P<0.05) than those of the susceptible pure stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Our results reinforce the view that the proportions of the different components of the mixture can compensate for weak heterogeneity in the susceptibility of the components, or reinforce the effect of strong heterogeneity (van den Bosch, 1993). The model showed that the higher the proportion of the highly resistant cultivar present in a mixture with a moderately susceptible cultivar, the less severe the yellow rust, which is consistent with the recent empirical results reported by Huang et al (2011).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results reinforce the view that the proportions of the different components of the mixture can compensate for weak heterogeneity in the susceptibility of the components, or reinforce the effect of strong heterogeneity (van den Bosch, 1993). The model showed that the higher the proportion of the highly resistant cultivar present in a mixture with a moderately susceptible cultivar, the less severe the yellow rust, which is consistent with the recent empirical results reported by Huang et al (2011).…”
Section: Discussionsupporting
confidence: 92%
“…The fact that our theoretical findings are consistent with empirical results showing that rust dynamics can be controlled by a mixture consisting of one‐third of a susceptible cultivar and two‐thirds of a resistant cultivar (de Vallavieille‐Pope & Goyeau, ; de Vallavieille‐Pope, ) is further evidence of the credibility of the model. Moreover, the model confirms empirical findings reporting that the severity‐reducing effect of a resistant cultivar mixed with a moderately susceptible cultivar on wheat yellow rust was greater than that obtained when it was mixed with the same proportion of a susceptible cultivar (Aslam & Fischbeck, ; Huang et al ., ). Thus, we can conclude that the model is biologically relevant, and that it can be used for educational and research purposes to illustrate the principles of mixture theory and generate hypotheses about the deployment of resistant cultivars.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In recent years, landscape modification has been recognized as a proven way to improve insect pest management through simultaneously planting a variety of several crops . Additionally, using a mixture of cultivars with different resistance backgrounds has been successful in controlling wheat diseases . Thus, using a suitable mixture of cultivars is of great significance for optimizing or sustaining the ecological environment for production agriculture …”
Section: Introductionmentioning
confidence: 99%